Protocol for a pilot randomized controlled trial comparing plasma with balanced crystalloid resuscitation in surgical and trauma patients with septic shock. Issue 1 (23rd September 2018) - Wei, Shuyan; Kao, Lillian S; Wang, Henry E; Chang, Ronald; Podbielski, Jeanette; Holcomb, John B; Wade, Charles E
Abstract : Background: Septic shock is a public health problem with high mortality. There remains a knowledge gap regarding the optimal resuscitation fluid to improve clinical outcomes, and the underlying mechanism by which fluids exert their effect. Shock-induced endotheliopathy (SHINE) is thought to be a shared pathophysiologic mechanism associated with worsened outcomes in critically ill trauma and sepsis patients. SHINE is characterized by breakdown of the glycocalyx—a network of membrane-bound proteoglycans and glycoproteins that covers the endothelium. This has been associated with capillary leakage and microvascular thrombosis, organ dysfunction, and mortality. Biomarkers of SHINE have been shown to correlate with clinical outcomes in patients with septic shock. Interventions to mitigate SHINE may improve outcomes in patients with septic shock. In surgical/trauma patients with septic shock, initial plasma resuscitation as compared with balanced crystalloid (BC) resuscitation will mitigate biomarkers of SHINE and improve clinical outcomes. Methods: A pilot, single-center randomized controlled trial (RCT) will compare initial plasma to BC resuscitation in surgical and trauma patients with septic shock. Patients will be enrolled based on a Sepsis Screening Score of ≥4 with a suspected source of infection. Patient randomization only occurs if they meet the criteria: (1) hypotension with mean arterial pressure <65 mm Hg, and (2) evidence of hypoperfusion including lactic acid >4 mmol/L, altered mental status or decreased urine output of <0.5 mL/kg in the past hour. Results: The primary outcome is a reduction in serum biomarkers at 6 hours. Secondary outcomes will include clinical outcomes such as intensive care unit-free days, organ dysfunction, and in-hospital mortality. Discussion: This trial will provide insights into the effects of initial plasma resuscitation on SHINE. Furthermore, it will provide unbiased estimates regarding the feasibility, safety, and clinical efficacy of plasma resuscitation in septic shock on which to base subsequent adequately powered multicenter RCTs. Trail registration number: ClinicalTrials.gov (NCT03366220 ).